Otimização do planejamento integrado de infraestrutura na exploração florestal na região Amazônica - Aguiar, Marcelo Otone (2019)
Sustainable Forest Management (MFS) has a key role in maintaining the remaining forest. Initiatives have been relied on new technologies for planning exploration to minimize environmental impacts and reduce operating costs. In this context, this research investigates optimization methods in order to propose a methodology to assist the manager in planning the allocation of infrastructures necessary for exploitation in native forests in the Amazon, minimizing environmental damage and maximizing the use of resources. This study was divided into three main sections. The first involves the evaluation of optimization methods for allocating storage yards. The second chapter was to evaluate methods for design forest roads. And finally, the third chapter investigates two methodologies for integrated allocation of forest roads, storage yards and skid trails. The study area was the Saracá Taquera National Forest (FLONA), located in the city of Faro, Oriximiná and Terra Santa, Forest Management Unit (UMF-1A), 2018 Annual Production Unit (UPA / 2018). The results of the first chapter indicate that, among the evaluated methods, the Simulated Annealing was the most efficient for the storage yard allocation. In the second chapter, the reported experiments show that the Dijkstra algorithm was the most effective and efficient for the road layout, considering that it was able to obtain optimal solutions in faster time than the other methods evaluated for the three considered instances. The results of third chapter indicate that evaluating different quantities in allocation of store yards may favor decision making, since yards directly influence optimal allocation forest roads and trails. In addition, it can be concluded that integrated planning allows choosing best overall plan solution, which is based on allocation of infrastructure set.